Impaired Neonatal Immunity and Infection Resistance Following Fetal Growth Restriction in Preterm Pigs - Bæk, Ole; Ren, Shuqiang; Brunse, Anders; Sangild, Per Torp; Nguyen, Duc Ninh (Frontiers in Immunology, 2020)
Background: Infants born preterm or small for gestational age (SGA, due to fetal growth restriction) both show an increased risk of neonatal infection. However, it remains unclear how the co-occurrence of preterm birth and SGA may affect neonatal immunity and infection risk. We hypothesized that fetal growth restricted (FGR) preterm newborns possess impaired immune competence and increased susceptibility to systemic infection and sepsis, relative to corresponding normal birth weight (NBW) newborns. Methods: Using preterm pigs as a model for preterm infants, gene expression in lipopolysaccharide (LPS) stimulated cord blood was compared between NBW and FGR (lowest 25% birth weight percentile) preterm pigs. Next, clinical responses to a systemic Staphylococcus epidermidis (SE) challenge were investigated in newborn FGR and NBW preterm pigs. Finally, occurrence of spontaneous infections were investigated in 9 d-old FGR and NBW preterm pigs, with or without neonatal antibiotics treatment. Results: At birth, preterm FGR piglets showed diminished ex vivo cord blood responses to LPS for genes related to both innate and adaptive immunity, and also more severe septic responses following SE infection (e.g. higher blood lactate, decreased blood pH, neutrophil and platelet counts, relative to NBW pigs). After 9 d, FGR pigs had higher incidence and severity of spontaneous infections (e.g. higher bacterial densities in the bone marrow), increased regulatory T cell numbers, reduced neutrophil phagocytosis capacity, and impaired ex vivo blood gene responses to LPS, especially when receiving neonatal antibiotics. Conclusion: FGR at preterm birth is associated with poor immune competence, impaired infection resistance, and greater sepsis susceptibility in the immediate postnatal period. Our results may explain the increased morbidity and mortality of SGA preterm infants and highlight the need for clinical vigilance for this highly sensitive subgroup of preterm neonates.